Hydrogen bonding framework in imidazole derivatives: Crystal structure and Hirshfeld surface analysis - Singh, Praveen; Kumar, Ranjeet; Tewari, Ashish Kumar (European Journal of Chemistry, 2020)
A series of imidazole derivatives (1-3) were synthesized with three component reaction among benzil, ammonium acetate and formaldehyde/aromatic aldehyde at 110 °C without a catalyst and solvent. These synthesized imidazole derivatives have shown intermolecular hydrogen bonding such as N-H···N and O-H···N. The imidazole 1 and 2 exhibited N-H···N intermolecular hydrogen bonding while imidazole 3 exhibited O-H···N intermolecular hydrogen bonding. The hydrogen bonds in imidazoles were studied by X-ray crystallography and Hirshfeld Surface Analysis at dnorm surface which show the visible red spots, indicated for hydrogen bonds. Further, Hirshfeld surface analysis also shows the percentage of all intermolecular interactions.